(untitled) (Modern education and development, 2025)
The cardiovascular system is essential for maintaining homeostasis by ensuring the transport of oxygen, nutrients, hormones, and waste products throughout the body. This paper provides an overview of the physiological mechanisms that regulate cardiac function and vascular dynamics, as well as the histological structure of the heart and blood vessels. Understanding the integration between form and function in this system is fundamental to the study of medicine and biomedical sciences.